Voorbij het koloniale perspectief: Indonesische bronnen en het onderzoek naar de oorlog in Indonesië, 1945-1949 - Bart Luttikhuis; Christiaan Harinck (BMGN: Low Countries Historical Review, 2017)
Challenging the colonial perspective: researching the war in Indonesia 1945-1949 with Indonesian sources Dutch historiography on the Indonesian War of Independence (1945-1949) has until this day remained almost exclusively dependent on Dutch primary sources. This article offers a first survey of new insights that can be gained by studying Indonesian archival records. Using several case studies of Dutch military violence, it sheds new light on four key aspects of counterinsurgent violence in the age of decolonization: the distinction between ‘civilians’ and ‘combatants’; the role of ‘low-key violence’ like arson and theft; the practise of mass-arrests; and the results of aerial, artillery and naval bombardments. The authors conclude that Dutch historiography as a consequence of selective use of sources has remained in the dark on the disruptive effects of Dutch warfare on Indonesian society. They argue for moving beyond the hegemony of the colonial perspective inherent to the colonial sources, by studying Indonesian archives more systematically. In de Nederlandse historiografie van de oorlog in Indonesië (1945-1949) wordt tot op de dag van vandaag vrijwel uitsluitend Nederlands bronnenmateriaal gebruikt. Dit artikel biedt een eerste inventarisatie van de nieuwe inzichten die de studie van Indonesisch archiefmateriaal kan verschaffen. Aan de hand van enkele casussen over Nederlands militair geweld wordt een viertal aspecten van de oorlogsvoering opnieuw belicht: de afgrenzing tussen ‘burgers’ en ‘combattanten’; de rol van ‘klein geweld’ zoals brandstichting en diefstal; de praktijk van massa-arrestaties; en de gevolgen van artilleriebeschietingen en luchtaanvallen. De auteurs concluderen dat de Nederlandse geschiedschrijving door selectief bronnengebruik blind is gebleven voor de ontwrichtende gevolgen van de Nederlandse oorlogvoering voor de Indonesische maatschappij. Zij pleiten daarom voor het doorbreken van de hegemonie van de Nederlandse bron en zijn koloniale perspectief door middel van een meer systematische studie in Indonesische archieven.